A (des) construção do discurso do corpo homossexual masculino: uma trajetória histórica da desnaturalização dos dispositivos de poder - Araújo, Jair Bueno de (2011)
The issue of homophobia in society has been relegated to the background or often to their own silence and concealment. This work has, therefore, as one of its main goals, begin to break the social silence surrounding this issue by studying homophobia related to the construction and hierarchy of binary sexual identities, heterosexual and homosexual. To carry out the discussion on this issue will be made, first, an analysis of political and social constructions of denaturalization of heterosexuality, as well as the compulsion of a sexuality that has been atrocious for centuries by imposing social and ideological institutions that constitute this same society that marginalizes the homosexual issue in favor precisely the realization of the heterosexual norm. Then, and as finalization of this work will be established a relation between this analysis and the movie "Encontrando Bianca," which is part of the kit (Kit Gay) against homophobia, prepared by the Ministry of Education in order to be distributed to all public schools in Brazil and therefore try to reverse the marginalization that homosexuality was relegated. The purpose of establishing this relationship is primarily in the practice note that homophobic triggered in Brazilian society may be reproduced in the school environment, acting directly on self-esteem and social-emotional development of pupils cognitive homossexuais.